Funcionamiento Familiar e inteligencia Emocional en Internas de Enfermería. Universidad Nacional de Trujillo - Mejia Pretell, María del Carmen (2017)
The present study, correlational descriptive cross-sectional, whose objective was to determine the relation between the level of functioning family and the level of emotional intelligence of internal nursing, National University of Trujillo, 2016 Formed the sample universe was considered by 60 internal nursing of Trujillo headquarters. To collect data two instruments were used: Emotional Inventory of Bar On ICE: NA – A (1997); adapted by Ugarriza (2001), and Rating Scale of functioning family FACES III: created by Olson (1985), analysis of the relationship between the variables was performed using the statistical reliability test Chi Square Criterion. The results show that 53.3 percent of internal nursing showed high level; 45 percent of them had moderate level and, only 1.7 percent low level. Also, the findings show that 70 percent of internal nursing have demonstrated moderate level of emotional intelligence; 30 percent a low level of emotional intelligence. Not detected statistically significant relationship between both variables (p> 0.730).